(untitled) (World Bulletin of Public Health, 2022)
This study aimed to assess the outcomes of children with diabetes according to morbidity and mortality in Iraq. Where data and demographic information were collected from several hospitals, and patients whose information was entered in the hospital were recruited for a full year from 2020 and 2021. The design of this research was based on the establishment of a crosssectional study of 80 people, and they were divided into two groups (45 children with diabetes and 35 children without diabetes). The quality of life and quality of life for patients was measured through the HRQoL dependence, in addition to analyzing the data statistics and calculating the statistical differences between the two groups to find out the type of relationship generated Results. The total number of diabetic patients reached 80 children aged between 8-16 years in the Republic of Iraq; patients were distributed according to gender in the patient group (30 children’s boys, 15 children’s girls) as for the control group (18 children’s boys, 17 children’s girls) The study revealed a significant prevalence of children with type 1 diabetes for 20 patients and 19 in the group of patients, as for the control group, 20 children with type 1 and 10 children with type 2. The study revealed a high mortality rate for the patient group for ten patients with 22.2%, and for the control group, the death rate for two children with 5.7%, and a negative relationship between HbA1c and the children’s quality of life as both sexes